Age-related Changes in Cervical Sagittal Alignment: A Radiographic Analysis. Issue 19 (1st October 2019) - Tang, Ray; Ye, Ivan B.; Cheung, Zoe B.; Kim, Jun S.; Cho, Samuel Kang-Wook
Abstract : Study Design: Retrospective cohort study. Objective: To identify age-related changes in cervical sagittal parameters using standard radiographs. Summary of Background Data: Cervical sagittal balance is important for the maintenance of neutral head posture and horizontal gaze. Degenerative changes in the cervical spine that occur with aging may alter cervical sagittal balance, which can lead to chronic neck pain and predispose to various cervical spine pathologies. Methods: We performed a retrospective cohort study of 151 patients with lateral cervical spine radiographs taken at our institution between December 2017 and June 2018. Cervical sagittal parameters were measured, including C1 inclination, C2 slope, C2-C7 Cobb angle, cervical sagittal vertical axis (cSVA), cervical tilt, upper and lower C7 slopes, T1 slope, and T1 slope minus cervical lordosis (TS-CL). The association between age and cervical sagittal parameters was assessed using the Pearson correlation coefficient and a linear regression analysis. An analysis of variance (ANOVA) with Tukey adjustments was then performed to identify differences in cervical sagittal parameters among patients aged 18 to 39 years, 40 to 64 years, and >64 years of age. Results: There were positive correlations between age and C2-C7 Cobb angle (r = 0.231, P  = 0.004), upper C7 slope (r = 0.280, P  < 0.001), lower C7 slope (r = 0.283, P  < 0.001), and T1 slope (r = 0.189, P  = 0.020). Upper C7 slope (R 2  = 0.079) and lower C7 slope (R 2  = 0.074) had the strongest correlation with age in the linear regression analysis. The ANOVA found significant differences among the age subgroups in terms of C2-C7 Cobb angle ( P  = 0.002), upper C7 slope ( P  < 0.001), lower C7 slope ( P  < 0.001), and T1 slope ( P  = 0.031). Patients >64 years old had significantly higher C2-C7 Cobb angle, upper C7 slope, lower C7 slope, and T1 slope. Conclusion: Changes in cervical sagittal alignment with age are characterized by increased cervical lordosis and increased thoracic kyphosis. Level of Evidence: 3 Abstract : In this retrospective radiographic analysis of cervical sagittal alignment in 151 patients, age was positively correlated with C2-C7 Cobb angle, upper C7 slope, lower C7 slope, and T1 slope. Age-related changes in cervical sagittal alignment were characterized by increased cervical lordosis and increased thoracic kyphosis.